A comparison of referral patterns to a multispecialty eConsultation service between nurse practitioners and family physicians: The case for eConsult. Issue 3 (12th May 2015) - Liddy, Clare; Deri Armstrong, Catherine; McKellips, Fanny; Keely, Erin
Abstract: Purpose: To explore referral patterns of nurse practitioners (NPs) and family physicians (FPs) using an electronic consultation (eConsult) service, and assess their perspectives on the service's value to their patients and themselves. Data sources: A mixed methods study including a cross‐sectional analysis of utilization data drawn from all eConsults completed from April 15, 2011 to September 30, 2014, and a content analysis of NP survey responses completed from January 1 to September 30, 2014. Conclusions: A total of 4260 eConsults were included in the cross‐sectional analysis (3686 from FPs and 574 from NPs). In our sample, NPs directed more cases to dermatology and fewer cases to cardiology and neurology ( p < .0001) than did FPs, and were more likely to report that an eConsult led to new advice for a new or additional course of action (62.8% vs. 57.5%) and less likely to report it resulted in an avoided referral (35.5% vs. 41.8%, p = .005). NPs reported slightly higher levels of perceived value of eConsults for their patients and themselves. Implications for practice: Differences in use and impact of eConsult exist between NPs and FPs. NPs value the service highly for their patients and themselves. The service reduces potential inequities related to outdated payment and scope of practice policies.